Association between Trace Element Concentrations and Anemia in Patients with Chronic Kidney Disease: A Cross-Sectional Population-Based Study. (August 2019) - Pan, Chi-Feng; Lin, Cheng-Jui; Chen, Shu-Hua; Huang, Chi-Feng; Lee, Chun-Chuan
Anemia is common in chronic kidney disease (CKD) and may be affected by trace element concentrations. While the concentrations of trace elements are known to be altered in CKD, the relationship between trace element and hemoglobin concentrations has not been systematically investigated in a large cohort. This study aims to examine associations between trace element concentrations and anemia in patients with CKD. Data from the National Health and Nutrition Examination Survey collected from 2011 to 2014 were used for this analysis. The participants who were more than 20 years old were included. A total of 3057 participants were included; the final cohort was divided into two groups based on CKD status. The concentrations of hemoglobin, iron, zinc, and manganese were significantly lower in participants with than without CKD (all p<0.05). Multivariate analyses showed that in patients without CKD, hemoglobin concentrations correlated positively with iron, zinc, and cadmium (β=0.005, 0.009, and 0.33, respectively), but correlated negatively with copper levels (β=−0.002). In patients with CKD, hemoglobin concentrations correlated positively with cadmium and selenium, but negatively with copper levels (β=0.57, 0.007, and −0.008, respectively). The serum iron concentration was found to correlate positively with zinc, cadmium, and selenium, but negatively with copper and manganese concentrations in the total study population (all p<0.05). The associations between serum concentrations of trace elements and hemoglobin differ between patients with and without CKD. Further investigations are warranted to determine whether patients with CKD have distinct trace element requirements.